Formation of double-cone-shaped ZnO mesocrystals by addition of ethylene glycol to ZnO dissolved choline chloride–urea deep eutectic solvents and observation of their manners of growth. Issue 47 (11th November 2021) - Wagata, Hajime; Harada, Ginji; Nakashima, Eriko; Asaga, Motoki; Watanabe, Tomoaki; Tanaka, Yuya; Tada, Masaru; Yubuta, Kunio
Abstract : ZnO mesocrystals were grown in ZnO dissolved CU-DESs with addition of ethylene glycol. Their manner of growth was observed and discussed. Abstract : ZnO mesocrystals have been explored for various physical and chemical applications. In spite of effort by a number of researchers, it is still difficult to grow specific crystal shapes in an environmentally-friendly, simple, and large-scale fabrication pathway. In this study, we report on a facile fabrication of ellipsoidal and double-cone-shaped ZnO mesocrystals elongated along the c -axis by an ionothermal method in choline chloride–urea deep eutectic solvents (CU-DESs) with addition of ethylene glycol (EG). It was found that as high as 16.7 mass% of ZnO could dissolve in CU-DESs at a high temperature by forming zinc cyanate complexes. Addition of EG to the above concentrated ZnO dissolved CU-DESs caused precipitation of ZnO particles which were confirmed as mesocrystals with transmission electron microscope images and selected area electron diffraction patterns. The crystal growth process and shape evolution in the CU-DESs were investigated and discussed. Photoluminescence study with excitation by ultraviolet light showed that the ZnO mesocrystals showed strong ultraviolet emission and relatively weak visible emissions, suggesting their high crystal quality.